Exploratory study to examine the neuroendocrinological changes in typically developing adults during a music-related participatory practice using computer software - Sugiyama, Yosuke; Tanaka, Sanae; Komagome, Aiko; Yuhi, Teruko; Furuhara, Kazumi; Higashida, Haruhiro; Tsuji, Takahiro; Kikuchi, Mitsuru; Tsuji, Chiharu (Frontiers in Psychology, 2025)
There has been a growing recognition of the benefits of participating in art practices for promoting well-being and social connection. Despite this, only a limited number of studies have assessed the neuroendocrinological changes that might contribute to these benefits. In this exploratory study, we focused on a creative activity related to music composition using digital tools. The emergence of computer software to create music (CSCM) has lowered the barriers to musical technical skills and theory, making music composition more accessible. We examined whether incorporating CSCM into a music-making workshop would affect the levels of two hormones, oxytocin and cortisol, among healthy adults. These two hormones were chosen, because oxytocin is involved in prosocial behavior and bonding, while cortisol plays a role in the stress response. Considering the time it takes to learn and adapt to a typical customized CSCM, we simplified its use to allow participants to experience music-making within a short timeframe and set up two distinct workshops. One was individual music creation with the support of a facilitator (Dyad) and the other was music creation in a group (Group). Participants in the Dyad workshops showed increased oxytocin levels, whereas those in the Group workshops did not. Cortisol levels remained unchanged during the Dyad workshops, but decreased in the Group ones. These results suggest that neuroendocrinological changes may occur during music-making activities using computer software. This work highlights the potential value of CSCM-incorporated music-making activities, although further controlled studies are required to confirm these findings.